2014
DOI: 10.1073/pnas.1319810111
|View full text |Cite
|
Sign up to set email alerts
|

Switching brain serotonin with oxytocin

Abstract: Serotonin (5-HT) and oxytocin (OXT) are two neuromodulators involved in human affect and sociality and in disorders like depression and autism. We asked whether these chemical messengers interact in the regulation of emotion-based behavior by administering OXT or placebo to 24 healthy subjects and mapping cerebral 5-HT system by using 2′-methoxyphenyl-(N-2′-pyridinyl)-p-[ ]MPPF nondisplaceable binding potential (BP ND ) in the dorsal raphe nucleus (DRN), the core area of 5-HT synthesis, and in the amygdala/hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(106 citation statements)
references
References 55 publications
(72 reference statements)
7
97
0
2
Order By: Relevance
“…In the laboratory, variation in 5-HTTLPR predicts elevated arousal and decreased social interest in assays of social attention and social reward [134]. Moreover, there is new evidence that serotonin and OT interact in brain circuits implicated in emotion regulation and social behaviour in humans [135], thus linking two neuromodulatory systems previously implicated in arousal and social function. Thus, although the definitive studies on the repeatability, fitness consequences and heritability of personality styles and social skills in the wild remain to be conducted, current evidence suggests that individual variation in social behaviour arises, in part, from the adaptive influence of genes on neural circuits and neuromodulatory systems mediating social function [136].…”
Section: Biological and Behavioural Variation In The Quality Of Sociamentioning
confidence: 99%
“…In the laboratory, variation in 5-HTTLPR predicts elevated arousal and decreased social interest in assays of social attention and social reward [134]. Moreover, there is new evidence that serotonin and OT interact in brain circuits implicated in emotion regulation and social behaviour in humans [135], thus linking two neuromodulatory systems previously implicated in arousal and social function. Thus, although the definitive studies on the repeatability, fitness consequences and heritability of personality styles and social skills in the wild remain to be conducted, current evidence suggests that individual variation in social behaviour arises, in part, from the adaptive influence of genes on neural circuits and neuromodulatory systems mediating social function [136].…”
Section: Biological and Behavioural Variation In The Quality Of Sociamentioning
confidence: 99%
“…Здесь и далее на рис. 4,5,7,9,10: левая сторона -левая сторона мозга, правая сторо-на -правая сторона мозга; Ф -после введения физраствора, О -после введения окситоцина; p = 0,054 по содержанию ДА в левой коре между мышами контрольной (получавшие физра-створ) и опытной (получавшие окситоцин) группы Исследование уровня моноаминов в симметрич-ных структурах мозга мышей-изолянтов высоко-и низкоагрессивной линий выявило существенные различия как по базовому проявлению асимметрии, вызванной изоляцией (без влияния препаратов), так и по способности окситоцина влиять на функциони-рование моноаминергических систем мозга.…”
Section: результаты исследования и их обсуждениеunclassified
“…В пользу данного предположения свидетельствовали как данные о наличии оксито-циновых рецепторов на серотонинергических ней-ронах [7], так и наши результаты, полученные на мышах линии C57Bl/6 [2,5]. Однако действие ок-ситоцина на серотонинергическую систему у белых беспородных мышей проявлялось слабо: эффек-ты окситоцина заключались в повышении 5-ГИУК в правом стриатуме и в исчезновении исходного преобладания 5-ОТ в левой коре.…”
Section: результаты исследования и их обсуждениеunclassified
“…OXT fibers project to numerous other brain regions, among them the amygdala, the nucleus accumbens and dorsal raphe nucleus, thus building local networks with GABAergic, dopaminergic and serotonergic circuits. [12][13][14] For instance, during birth, OXT mediates the reduction of intracellular chloride concentrations, leading to a shift in GABAergic currents from excitatory to inhibitory. [14] Intriguingly, it is suggested that autism might partly be caused by an incomplete execution of this shift.…”
Section: Genes and Behavior -The Impact Of Genetic Variances Of The Omentioning
confidence: 99%
“…It is speculated that OXT brings about its anxiolytic effect partly via modulation of 5-HT activity within the amygdala, providing new possibilities for therapeutic strategies. [12] Furthermore, there is good evidence for interactions of OXT with the dopaminergic system, especially within the nucleus accumbens, where OXT promotes the rewarding effects of, for example, social interactions. [13] Moreover, there is also evidence for OXT interactions with the glutamatergic system, specifically with mGluR5 in the septum.…”
Section: Genes and Behavior -The Impact Of Genetic Variances Of The Omentioning
confidence: 99%